Land as a source of revenue mobilisation for local authorities in Ghana (Journal of Science and Technology, 2016)
Local government finance poses problems to many governments in the developing world. This is notwithstanding the fact that local authorities are at the forefront of local development efforts. In Ghana, the central government is enjoined by the country's constitution to devolve at least five percent of the national revenue to local authorities annually. For many local authorities, this has become the main source of finance. Though there are other sources of finance available to the local authorities, these have been deemphasised by most local authorities. The paper postulates that the land resources of the local authorities provide a veritable source of local revenue which has not been fully tapped by the authorities. Apart from the property rate which all local authorities in the country levy, little attention is paid to the potential of the land resources of the local authorities as sources of revenue. The paper presents some opportunities available to the local authorities to raise money from their land resources.